2020
DOI: 10.1186/s40634-020-00265-3
|View full text |Cite
|
Sign up to set email alerts
|

Absence of instabilities and intra-prosthetic dislocations at 7 to 11 years following THA using a fourth-generation cementless dual mobility acetabular cup

Abstract: Purpose: Dual-mobility (DM) cups are increasingly used in total hip arthroplasty (THA) but there lacks literature on their long-term results. We aimed to investigate outcomes of a fourth-generation cementless DM acetabular cup at 7-11 years. Methods: We retrospectively evaluated 240 consecutive hips that received cementless THA using the same dual mobility cup (Novae Sunfit TH) and femoral stem (Corail). Patients were recalled at ≥7 years to collect Oxford hip scores (OHS), Harris hip scores (HHS), and inspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…This study demonstrated satisfactory clinical outcomes of uncemented THA using a novel hemispherical DM acetabular cup without a protrusive cylindro-spherical rim, with a cup cumulative revision rate of 0.6%, and a global cumulative revision rate of 1.5%, at a mean follow-up of 2.8 years. While the global cumulative revision rate may seem high at such short follow-up, it is worth noting that some revisions were due to traumatic periprosthetic fractures and that the rate remains within the range reported for other contemporary DM acetabular cups [ 4 , 6 , 7 ]. Numerous smaller series (<100 hips) had no revisions of any kind at 5 to 10 years of follow-up, but larger cohorts (>150 hips) had overall revision rates between 0.5% and 3.6%, at 5 to 13 years of follow-up.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This study demonstrated satisfactory clinical outcomes of uncemented THA using a novel hemispherical DM acetabular cup without a protrusive cylindro-spherical rim, with a cup cumulative revision rate of 0.6%, and a global cumulative revision rate of 1.5%, at a mean follow-up of 2.8 years. While the global cumulative revision rate may seem high at such short follow-up, it is worth noting that some revisions were due to traumatic periprosthetic fractures and that the rate remains within the range reported for other contemporary DM acetabular cups [ 4 , 6 , 7 ]. Numerous smaller series (<100 hips) had no revisions of any kind at 5 to 10 years of follow-up, but larger cohorts (>150 hips) had overall revision rates between 0.5% and 3.6%, at 5 to 13 years of follow-up.…”
Section: Discussionmentioning
confidence: 87%
“…According to recent literature, sepsis is a common reason for revision of DM cups, and this could be a result of the frailty and comorbidities of the elder population in which they are usually implanted [ 1 , 7 , 15 ]. The present study recorded no revisions due to infection at 2.8-year follow-up, thus comparing favourably to that reported in the Danish Hip Registry for all THA infections (1.0% at 5 years) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical and radiographic outcomes of cementless DMCs are excellent at medium and long follow-ups with an overall survivorship of 95% at 10-year follow-ups and demonstrated low revision and dislocation rates, without major polyethylene wear concerns [ 16 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,14 The available literature that was reviewed shows no cases of early IPD occurring in patients with a femoral head smaller than 28 mm or in patients in which the DMC was used in conjunction with a skirted femoral head. 9 Chouteau et al 19 reported no cases of IPD in their cohort of 240 fourth-generation DMCs at 7-to 11-year follow-up, highlighting the rarity of the complication in modern designs and ultra-high molecular weight polyethylene. The potential for polyethylene wear with subsequent IPD still exists and may present several years after implantation.…”
Section: Modern Designsmentioning
confidence: 98%